Time-bound opportunity costs of informal care: Consequences for access to professional care, caregiver support, and labour supply estimates - Wolter Hassink; Bernard van den Berg (Institute for the Study of Labor (IZA), 2011)
Patterns of informal care are documented throughout the day with Dutch time use diary data. The diary data enable us to identify a, so far overlooked, source of opportunity costs of informal care, i.e. the necessity to perform particular tasks of informal care at specific moments of the day. Some care tasks are relatively unshiftable, while other tasks are shiftable implying that they can be performed at other moments of the day or even on different days. In particular, household and organization activities seem to be shiftable for employed caregivers, while personal care seems to contain unshiftable activities. This implies an additional opportunity cost of providing personal care tasks. As the care recipient's need for care may be related to the possibility to shift informal care throughout the day, we conclude that one should be careful with using care need as an instrument of informal care in labour supply equations.
urn:nbn:de:101:1-201104113069
Keywords: J2; I3; 330; use of time; joint production; informal care; paid work; opportunity cost; labor supply; Familienpflege; Opportunitätskosten; Pflegedienst; Arbeitsangebot; Zeitbudgetforschung; Schätzung; Niederlande